CSR Communication of Petrogas (Basin) Ltd on Stunting Reduction in Arar Village - Sorong Regency - Abdul Rahman Hardiansyah; Vilya Dwi Agustini; Farida Hariyati (Hasanuddin University, 2025)
Corporate Social Responsibility (CSR) is one of the strategies used by companies to support this effort. Communication plays an important role in the success of Corporate Social Responsibility (CSR) programs, especially in health issues such as stunting reduction. Stunting is a significant health problem in Indonesia, including in Southwest Papua, with long-term impacts on children's physical growth, cognitive development, and quality of life. The Indonesian government has issued various policies to accelerate the reduction of stunting, one of which is through nutritional interventions and cross-sector collaboration. This study aims to examine the communication of CSR programs carried out by Petrogas (Basin) Ltd. in an effort to reduce stunting in Arar Village, Sorong Regency. Through the program of providing additional food for toddlers and pregnant women. The research method used is a qualitative approach with in-depth interviews, observation and literature study. The results showed that effective communication in CSR programs plays an important role in the successful implementation of providing supplementary programs for toddlers and pregnant women. In addition, the active involvement of beneficiaries and stakeholders in the communication process increases the effectiveness of the program and strengthens the relationship between the company and the community. This research provides insight into how CSR communication can contribute to addressing public health issues and building a positive corporate image.